The Development Of Discovery Learning-Based Student Worksheets On Circle Materials For Class Viii Students At Smp Muhammadiyah 2 Bambanglipuro - jumaini rahmadani; Rima Aksen Cahdriyana (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2022)
The low level of literacy and awareness of students in doing assignments is one of the factors that slows students' progress in learning, with this LKPD it is expected to be able to motivate students to improve learning literacy and encourage students to work on independent/group assignments. This study aims to produce learning discovery worksheets based on circle material for class VIII, and to find out the product in terms of validity and practicality.This study uses ADDIE development, the research was conducted at SMP Muhammadiyah 2 Bambanglipuro, odd semester 2021/2022, with research subjects in small class trials involving 5 students and large class trials involving 16 students. The instrument used is a questionnaire. The data analysis technique used is to process qualitative data to calculate the validity and practicality scores of the developed media.The results showed that the average LKPD assessment by material experts was 4.2 with very valid criteria, for the average LKPD assessment by media experts was 4.3 with very valid criteria. Meanwhile, the average for small class trials is 4.2 in the very practical category, and the average for large class trials is 3.9 in the practical category. Thus, discovery learning-based worksheets get valid and practical categories, so they are feasible to be used as learning media.